(untitled) (Fenestella. Inside Medieval Art, 2021)
The text analyzes the ornamental culture of the monastery of San Vincenzo al Volturno, through the comparison between different classes of materials. Through the analogies between the ornamental motifs, we tried to reconstruct their creative process, on a perceptual basis. The study, in fact, focuses on the relationship between the individual and the environment, exploiting the theories of Gibson, applying them to a particular context such as monasteries. The goal is to demonstrate how the continuous use of space determines the acquisition of visual information, which, stored in memory, is re-proposed during the creative process. Especially, it is the daily journey of the rooms that guarantees the memorization of the signs and, at the same time, their updating, through the change of perspective that occurs with movement. In the last part, we discuss the perceptive effects of the aniconic paintings in the crypt of Joshua.